What Influences Trust in Survey Results? Evidence From a Vignette Experiment. (29th July 2022) - Stadtmüller, Sven; Silber, Henning; Beuthner, Christoph
Abstract: More survey results are available today than ever before. This increase in survey data has been accompanied by growing concerns about their quality. With the present study, we aim to investigate to what extent the public draws on survey quality information when evaluating the trustworthiness of survey results. We implemented a vignette experiment in an online panel survey ( N = 3, 313), in which respondents each received four different survey descriptions with varying methodological information. Compared with respondent characteristics, survey quality information had only a minor effect on perceptions of trustworthiness. However, trust in the survey results was significantly influenced by sample size and sample balance. Finally, the relevance of survey quality information increased with the cognitive ability of the respondent.